Generalized multiprotocol label switching an overview of routingand management enhancements. - Banerjee, A. (IEEE Communications magazine)
Generalized multiprotocol label switching, also referred to as multiprotocol lambda switching, supports not only devices that perform packet switching, but also those that perform switching in the time, wavelength, and space domains. The development of GMPLS requires modifications to current signaling and routing protocols. It has also triggered the development of new protocols such as the Link Management protocol. We present the traffic engineering enhancements to the Open Shortest Path First Internet routing protocol and ISIS Intradomain Routing Protocol, two popular routing protocols, to support GMPLS. We present the concepts of generalized interfaces, label-switched path hierarchy, and link bundling intended to improve GMPLS scalability. We also discuss the Link Management Protocol which can be used to make the underlying links more manageable